12 nJ 2 μm dissipative soliton fiber laser. (25th March 2015) - Yang, Nan; Huang, Chongyuan; Tang, Yulong; Xu, Jianqiu
Abstract: We report high-energy 2  μ m dissipative soliton generation from a passively mode-locked thulium-doped fiber laser with a semiconductor saturable absorber mirror. Self-starting stable mode-locking has been achieved with pulse energy of 12.07 nJ, pulse width of 43 ps and average power of 263 mW at a repetition rate of 21.79 MHz. The laser spectral width is ~2.65 nm with a center wavelength of 1928.2 nm. To the best of our knowledge, this is the highest single pulse energy reported to date directly from a passively mode-locked thulium-doped fiber laser.